A review on boilers energy use, energy savings, and emissions reductions. (November 2017) - Barma, M.C.; Saidur, R.; Rahman, S.M.A.; Allouhi, A.; Akash, B.A.; Sait, Sadiq M.
Abstract: Boiler is a widely used steam generating system in industries and power plants. A significant portion of the world energy consumption is being used in boilers. A small improvement on the boiler efficiency will help to save a large amount of fossil fuels and to reduce CO2 emission. This study describes the amount of energy used in boilers, ways employed to evaluate their energy efficiency, losses occurred and their causes, ways of waste heat recovery and minimizing heat loss using technologies, role of maintenance activities, and technical education to make people aware of the energy usage. Latest published literature on the above mentioned topics which includes PhD and MSc theses, journal articles, conference proceedings, reports and web materials have been reviewed and reported. It is found that a substantial amount of energy is wasted through high temperature flue gas or exhaust of the boiler. Also, some other unavoidable losses occurr due to various reasons. However, waste heat could be recovered using different technologies as a useful form of energy such as electricity, heat, refrigeration effect, etc. The efficiency of the boiler can be improved by doing scheduled maintenance work, which helps to run a boiler at its highest efficiency. In order to create awareness about energy use, education programs and seminars need to be arranged on regular basis for the staff involved. This will help them to understand the importance of the energy as being used in the boiler system as well as the impact of their actions during the operation of the boiler.